(untitled) (مجلة ديالى للبحوث الانسانية, 2023)
The study aimed to assess EFL learners’ ability to use grammatical cohesive devices, to identify the types of grammatical cohesive devices which are frequently used in EFL learners’ descriptive essays, to find out the problematic areas related to grammatical cohesion in Iraqi EFL learners’ essays, and to suggest appropriate strategies for enhancing learning abilities to use cohesive devices. The study followed the descriptive analytical method. Two tools were used as a means of data collection; a questionnaire and a test were distributed and administrated among (50) students from Iraqia university. The collected data were analyzed statistically by using the Statistical Packages for Social Sciences Programmer (SPSS). The study comes up with many results, the important of which are: the majority of Iraqi EFL learners are not able to use English Grammatical cohesive devices in their English essay, students have no ability to use cohesive devices such as consequently, to sum, theirs, you, yours, students lack the ability of receiving instruction on how to use or interpret ellipsis and substitution devices. The study recommends the followings, the important of which are: there should be more exposure to cohesive devices through many texts and sources, students can improve their writing by practicing more exercises at home, students should be aware of the functions of grammatical devices, and learners should have a time table for learning grammatical cohesive devices .